Evaluation of the sigma phase precipitation in duplex stainless steel by nondestructive testing - Silva, David Domingos Soares da (2020)
Duplex stainless steels (DSS) have a structure composed of α-Fe and γ-Fe in approximately equal volume fractions. Which provides an excellent integration between mechanical properties and corrosion resistance. However, the precipitation of sigma (σ) phase may cause a severe deterioration of these properties, phenomenon known as sigma phase embrittlement. In the present work, the effect of the isothermal aging treatment at 800 °C (temperature in which σ phase can be formed) on metallurgical, corrosion, magnetic and mechanical properties on DSS UNS S31803 was investigated. In addition, two new nondestructive methods for monitoring of sigma phase embrittlement in DSS were proposed and evaluated. The first method is based on the electromechanical impedance (EMI), using piezoelectric sensors. The basic idea of this method is that the increase mechanical stiffness, due to sigma phase embrittlement, will leads to the variation in the EMI signatures. The second method, designated as low-fields magnetic analysis (LFMA) is based on the measurement of magnetic flux density. Once the precipitation of σ phase cause a change in the volume fraction of α-Fe/γ-Fe phases due to α-Fe (ferromagnetic phase) decomposition to precipitate σ (paramagnetic phase). The evaluated techniques present accurate results with high sensitivity and reliability.